The Unfairness of (Poverty) Targets - Allwine, Melanie (Oxford University Press, 2016)
The evaluation of policy performance against set targets is rarely adjusted to the heterogeneity in the initial distribution of characteristics. Building on previous literature, we propose a framework to account for differences in initial characteristics in evaluating policy performance. We apply the proposed framework to the appraisal of poverty reduction and show that initial characteristics can considerably affect performance. The framework advances by explicitly quantifying the importance of the non-linearity of the growth elasticity of poverty reduction. Whilst wealthier countries did perform better in reducing poverty during 1995–2008, after equalizing the mean of the initial distribution of income the situation reverses, with the poorest countries going from being the worse to being the best performers in poverty reduction.